A Process and Outcome Evaluation of a One-Semester Faculty Learning Community: How Universities Can Help Faculty Implement High Impact Practices - Susan D. Einbinder (Park University, 2018)
This process and outcome qualitative study describes and critically assesses the experiences of the faculty who participated in the one-semester FLC addressing CLTs through a content analysis of individual narratives completed at the end and ten months after the FLC ended. The existence and contributions of four prerequisites for successful collaboration (Einbinder, Robertson, Garcia, Vuckovic & Patti, 2000) are introduced to explain this FLC's success and then extended to suggest how future FLC initiatives can expand and improve on these accomplishments.